Pembagian Harta Bersama Menurut Hukum Islam - Sholihah, Hani (Fakultas Syariah IAIN Purwokerto, 2007)
The rule on dividing joint property and wealth between a husband and a wife is based on the customary law (‘urf) which divides half of those wealth for each. This rule is also determined in UU No 1/1974 (Code of Mariage). Actually, ‘urf is only a kind of consideration in defining the law and that should not be opposed to any rules.